Global magnetic field of the Sun as a star and of convective stars - Plachinda, S. (Известия Крымской астрофизической обсерватории, 2007)
The report is dedicated to Andrew Severny memoryIn terms of the Babcock’ and Leighton’ phenomenological magneto-kinematic model of the solar cycle and in terms of standard α-Ω dynamo theory, there are only two main 0 components of large-scale magnetic field on the Sun: toroidal magnetic field and poloidal field. The first results of the magnetic field measurements of the Sun as a star were published by A. Severny, and named as General Magnetic Field (GMF) of the Sun as a Star. What is the origin of the GMF?Using frequencies for P1 = 26.929 ± 0.015 d and P2 = 27.144 ± 0.015 d, we can obtain main periods in the power spectrum for GMF of the Sun as a star including period of activity cycle. One of the initial periods is due to a rigid rotation of radiative zone, and the second one is produced by differential rotation of the Sun’s top layer. The Origin Magnetic Field of the Sun’s radiative zone is captured by moving matter and transported up to the surface, where a beating of two main frequencies produces observing picture.The presence of weak general magnetic field (up to some dozen Gausses) for 21 convective stars (F9-M3 spectral types and I-V luminosity classes) is detected nowadays. For two solar-like stars variations of the GMF as a function of the stellar rotation has been determined: for more active and more young star than the Sun ξ Boo A (G8 V) with Prot = 6.198 d, and for old solar-like star 61 Cyg A (K5 V) with Prot = 36.617 d. For ξ Boo A GMF variations as a function of rotational period was confirmed using MuSiCoS Stokesmeter in 2003. The Crimea curve (1990−1999) shows domination of the dipole component contrary to the MuSiCoS curve for 2003 year, which demonstrates the presence of quadrupole component. An existence of the GMF on convective stars with vigorous convective envelopes confirms a hypothesis that the GMF is a real phenomenon.GMF reflects properties of a stationary global magnetic field of the Sun’s (convective star’s) radiative interior on its surface, and there appears to be the third large-scale component of the magnetic field.